2002
DOI: 10.1115/1.1503795
|View full text |Cite
|
Sign up to set email alerts
|

An Automated Approach for Direct Measurement of Two-Dimensional Strain Distributions Within Articular Cartilage Under Unconfined Compression

Abstract: An automated approachfor measuring in situ two-dimensional strain fields was developed and validated for its application to cartilage mechanics. This approach combines video microscopy, optimized digital image correlation (DIC), thin-plate spline smoothing (TPSS) and generalized cross-validation (GCV) techniques to achieve the desired efficiency and accuracy. Results demonstrate that sub-pixel accuracies can be achieved for measuring tissue displacements with this methodology with a measurement uncertainty ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

20
176
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 189 publications
(200 citation statements)
references
References 48 publications
20
176
4
Order By: Relevance
“…Unlike previous 2D studies that documented strains perpendicular to the thickness direction either as generally zero [23,29] or at least an order of magnitude smaller than strains in the thickness direction [34], strains perpendicular to the thickness direction reported herein were in general large and on the same order as strains in the thickness direction. This primary difference can be attributed to the loading protocol used (i.e.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Unlike previous 2D studies that documented strains perpendicular to the thickness direction either as generally zero [23,29] or at least an order of magnitude smaller than strains in the thickness direction [34], strains perpendicular to the thickness direction reported herein were in general large and on the same order as strains in the thickness direction. This primary difference can be attributed to the loading protocol used (i.e.…”
Section: Discussioncontrasting
confidence: 99%
“…strain at equilibrium versus strain during cyclic loading). Another study reported that all strain components changed nonlinearly with increasing load [34], which is in contrast to the results reported herein for strain in the split-line and transverse directions. Further, the large strains observed were not unexpected based on rapid loading of the explants (in less than 200ms [24]) and the resulting pressure gradient in favor of interstitial fluid flow towards the outer boundary of the cylindrical cartilage samples [l].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Due to the inhomogeneous depth-dependent properties of articular cartilage [27,32], there has been increased interest in developing methods to replicate this inhomogeneity and study its importance. A recently developed K. W. Ng et ul.…”
mentioning
confidence: 99%